توجيه التعارض بين أحاديث هدم الكعبة وكونها حرما آمنا - النعيمات، أمل عبدالله محمد (جامعة آل البيت, 2020)
جاء هذا البحث لتوجيه التعارض بين كون الكعبة حرماً آمناً والأحاديث التي تخبر عن هدم الكعبة، وقد جعلت البحث في مقدمة، وخمسة مباحث، كان المبحث الأول: حول التعارض، والثاني عن بناء الكعبة، والثالث حرمة الكعبة قبل الاسلام وبعده، أمّا المبحث الرابع؛ فقد عرضت فيه النصوص الدالة على هدم الكعبة، والمبحث الخامس كان في: التوفيق بين الأحاديث الدالة على هدم الكعبة والآيات الدالة على كونها حرماً آمناً. واعتمدت الدراسة المنهج الاستقرائي والمنهج التحليلي، وخلصت إلى أنه لا يوجد تعارض حقيقي بين أحاديث هدم الكعبة والنصوص الدالة على كونها حرماً آمناً، وأن بقاء الحرم آمناً لا بد له من شروط، ومن أعظمها ظهور التوحيد، وغلبته وأن أحاديث هدم الكعبة، هي من دلائل نبوته صلي الله عليه وسلم، وأن فيها البشارة بغلبة الإسلام، وبقائه ما تمسك به أهله، ودعو إليه، كما يؤخذ منها تحذير أمة الإسلام من التقاعس عن التبليغ؛ مما يؤذن بعلو شأن الكفر وغياب التوحيد؛ وزوال المنة وهدم الكعبة؛ وهذا من عاجل العقوبة للبشرية؛ لقاء كفرها بربها، وأنَ هذا كائٌن قبيل قيام الساعة.
This research resolves the conflict of evidence about the Ka’bah being a sacred and secure place and the ahadith that tell us about its destruction. It is divided into an introduction and five sections, the first section discusses conflicting texts, the second about the building of al-Ka’bah, the third presents its sacredness both before and after Islam, the fourth presents the texts that tell us about the destruction of al-Ka’bah, and the fifth section is about resolving the conflict between its being a sacred and secure place and the news about its destruction, in a conductive and analytical way. The study reached the conclusion that there is no any real conflict between the destruction of the Ka’bah and the texts that describe it as a sacred and secure place, and that the security of the sacred mosque has its conditions, amongst which is that Oneness should prevail, the ahadith about the destruction of Ka’bah are of the signs of the prophet-hood of prophet Muhammad, and the existence of Ka’bah indicates the strength and power of Islam, and the hadith in question warns Muslims against weakness in conveying the message of Islam, as if this happens, then Allah’s bounty may be removed and the Ka’bah will be destroyed as a quick punishment of humanity and a result of its belief.
Keywords: الشريعة الإسلامية -- الأحاديث النبوية -- هدم الكعبة -- الحرم المكي